2020
DOI: 10.1002/pbc.28605
|View full text |Cite
|
Sign up to set email alerts
|

Different 18F‐FDG PET parameters for the prediction of histological response to neoadjuvant chemotherapy in pediatric Ewing sarcoma family of tumors

Abstract: Background: The histological response to neoadjuvant chemotherapy (NAC) in pediatric patients with Ewing sarcoma family of tumors (ESFT) can predict the disease-free survival. Therefore, a noninvasive method for response assessment is needed. Using the currently established imaging modalities, mass reduction does not always correlate with the percentage of necrosis. Objective: To determine the potential role of 18 fluorine-labeled fluoro-2-deoxyglucose positron emission tomography (18 F-FDG PET) metabolic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
(25 reference statements)
3
7
0
Order By: Relevance
“…Nevertheless, poor histologic response was significantly associated with lower PFS rates and shorter median PFS compared to the responder group in the Kaplan–Meier survival analysis, similar to the results of previous studies [13,17]. In previous studies, it was reported that the quantitative metabolic-volumetric FDG PET derived parameters were found to be significantly associated with histologic tumor response 13,17,19–21. These studies were generally based on the quantitative values of FDG PET imaging after NAC and the percentage changes between on baseline and post-therapy scans.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, poor histologic response was significantly associated with lower PFS rates and shorter median PFS compared to the responder group in the Kaplan–Meier survival analysis, similar to the results of previous studies [13,17]. In previous studies, it was reported that the quantitative metabolic-volumetric FDG PET derived parameters were found to be significantly associated with histologic tumor response 13,17,19–21. These studies were generally based on the quantitative values of FDG PET imaging after NAC and the percentage changes between on baseline and post-therapy scans.…”
Section: Discussionsupporting
confidence: 84%
“…However, in a most recent, although retrospective, study, in patients with localized ESFT [ 92 ], ΔTLG revealed the best prediction for histopathological response with 100% sensitivity and 77.8% specificity. Finally, it is important to mention that when dichotomizing end-treatment (post-induction chemotherapy) MTV/TLG values, calculated by fixed “absolute” and “liver-based” thresholds [ 91 ], a correlation with good or poor histopathological response was revealed, in agreement with another prospective study, most recently published on pediatric ESFT patients [ 93 ] ( Table 1 ).…”
Section: Pediatric Sarcomassupporting
confidence: 81%
“…Initial studies evaluating metrics such as PSMA-TV and TL-PSMA for metabolic response assessment have shown promising results, some of these through a 'PSMA-modified' RECIST or PERCIST classification system. Importantly, several studies reported an association of these PSMA PET parameters with overall survival (OS) during treatment with radioligand therapy (RLT) with 177 Lu-PSMA (89)(90)(91). A recent systematic review summarized the available evidence for using quantitative PSMA parameters versus serum PSA in assessing response for castration-resistant prostate cancer (92).…”
Section: Prostate Cancermentioning
confidence: 99%
“…Furthermore, MTV can be combined with metrics of tumor distance within a patient to not only represent volume, but also dissemination for better reflecting prognosis, as shown in NHL (175). Evaluation of the changes in MTV and/or TLG have been shown to outperform PERCIST-based approaches in tumors with frequent bone lesions, such as Ewing sarcoma and osteosarcoma (177)(178)(179)(180). Volumetric determination on PET is not hampered by bone/soft tissue interfaces, taking the total tumor burden into account in combination with the metabolic activity.…”
Section: Beyond Recist and Percistmentioning
confidence: 99%